The Effect of Date (Phoenix Dactylifera) Juice to Increase Haemoglobin Level of White Rat (Rattus Novergicus). - Yani Sodiqah (UMI Medical Journal, 2016)
This experiment has conducted on march – April 2015.Background: High Prevalence of anemia in Indonesia, especially defficincy anemia, need several nutrition approaches. Date fruit (Phoenix dactylifera) consist of 23 kinds of amino acyd that make high concentration of protein (2.3% - 5.6 %) higher than other fruits. With other substances like Carbohidrat ( total 44%-88%) , fat (0,2% -0,4%), fiber (6,4%-11,5%), minerals and vitamins, date fruit should be usefull for therapy of anemia. There are several commercial date juice product that should be proved to be a herbal therapy of anemia.Objective: This research aims to know the effect of date (Phoenix dactilafera) juice toward hemoglobin level in white rat blood (Rattus novergicus).Research Method: Twenty four (24) white, male, adult, health and clean rat with weight around 100-200 gr (Rattus novergicus) are divided into four (4) groups. The rats are adapted for seven (7) days, then be measured its hemoglobin degree. Next, they are given with Na 10-20 mg each rat for seven (7) days. The next step is giving date juice 3 cc per oral, given in three groups with three different brands for three days, while the control group is not given date juice. Then, it is done to measure haemoglobin level by using hemoglobin Hb strip easy touch.Result : The issue of date juice (Phoenix dactilafera) in all tested brands can increase hemoglobin level of white rat (Rattus novergicus) with different percentage. The increasing of hemoglobin level is reached by each brand. The highest rate is taken by Date juice “AJ” (63,7 %) or 7,0 point, then followed by date juice” S” (36,8%) or 4,4 point, and date juice “T” (8,7%) or 1,1 point. In the meantime, the control group is around 6,7 % or 0,93 point. Statistically, the increasing of white mice hemoglobin level is significantly just reached by giving Date juice “AJ”, justified by one-way ANOVA ( P = 0,0099).Conclusion :The date juice (Phoenix dactilafera) increase the hemoglobin level of white rat (Rattus novergicus)